Attitude and approach to acquiring health knowledge and their influencing factors among employees in public places: a cross-sectional survey in Zhejiang province - Ming-luan XING; Xue-qing LI; Li-zhi WU (Zhongguo gonggong weisheng, 2022)
ObjectiveTo explore the status and influencing factors of attitudes and approaches to acquiring health knowledge among employees in public places in Zhejiang province. MethodsA face-to-face survey was conducted among 1 296 employees working in hotels, public baths/swimming pools, hair/beauty salons, and waiting rooms for buses/trains in 4 prefectures/municipalities of Zhejiang province in 2019. Participants′ information on attitude and approach to acquiring health knowledge were collected with a questionnaire compiled by researchers of Chinese Center for Disease Control and Prevention. Logistic regression was used to analyze main factors influencing the approach for health knowledge acquisition. ResultsOf the 1 290 valid respondents, 986 (76.43%) reported objective need to acquire health knowledge, 1 092 (84.65%) reported the willingness to acquire the knowledge, and 1 085 (84.11%) reported ever obtaining the knowledge actively. The respondents′ attitude towards health knowledge acquisition differed significantly by age, gender, education attainment, and work type (P < 0.05 for all). Among all the respondents, the top three approaches to acquire health knowledge were through internet surfing (reported by 89.77% of the respondents), from administrators' publicities (89.38%), and via watching television programs (87.29%). The results of logistic regression analysis revealed that higher education (college and above vs. primary school or lower) and higher annual household income (more than 200 000 vs. less than 50 000 RMB yuan) were promoting factors for acquiring health knowledge through internet surfing, with the odds ratio (OR) (95% confidence interval [CI]) of 6.819 (3.005 – 15.471) and 5.268 (1.235 – 22.465); compared to those being cleaners, the respondents being engaged in technical tasks were less likely to acquire health knowledge from administrators′ publicities (OR = 0.367, 95% CI: 0.187 – 0.720); and female gender (versus male: OR = 1.720, 95% CI: 1.209 – 2.446) and higher education (college and above vs. primary school or lower: OR = 3.438, 95% CI: 1.608 – 7.352) were promoting factors for acquiring health knowledge via watching television programs. ConclusionAmong employees working in public places in Zhejiang province, the attitude towards health knowledge acquisition needs to be improved and special attention should be paid to the approach for health knowledge acquisition and the employees′ characteristics when developing related projects.